Structural transformation, income inequality and government expenditure: evidence from international panel data - Wannaphong Durongkaveroj (Penerbit Universiti Kebangsaan Malaysia, 2022)
In the past few decades, several developing countries have experienced a notable increase in income inequality along the path of economic development. Widening income inequality has been accompanied by growing demand for redistributive policy measures. The purpose of this paper is to examine the government spending and income inequality nexus in the context of structural transformation using an international panel data set covering 51 countries over the period 1990 to 2018 and an analytical framework that draws on Kuznets (1955). The system GMM estimates show that an expansion of government expenditure first generates rising income inequality but falling at the later stage, suggesting an inverted U-shaped relationship. Compared to developed nations, this inequality-reducing effect of government expenditure is more pronounced in developing countries. In addition, the relationship also varies by specific types of government expenditure and sample composition. For instance, inequality–reducing effect of government spending in Asian countries is only limited to health expenditure, indicating that the redistributive impacts of government expenditure may partly depend on the extent to which the primary beneficiaries of such spending are low-income people.